2001
DOI: 10.1007/s001980170063
|View full text |Cite
|
Sign up to set email alerts
|

Bone Quality Parameters of the Distal Radius as Assessed by pQCT in Normal and Fractured Women

Abstract: The aim of this study was to test the ability of some indicators of different aspects of bone quality (assessed by peripheral quantitative computed tomography in the distal radius) to discriminate between fractured and nonfractured individuals. The study compared 214 women aged 45-85 years, free of any bone-affecting treatment, of whom 107 had suffered a Colles' fracture in the previous 6 months and 107 did not. The determinations included bone tissue or mineral 'mass' indicators (trabecular, cortical and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 40 publications
5
34
1
2
Order By: Relevance
“…Our results confirm and extend previous ex vivo studies on iliac crest bone biopsies that showed alterations of trabecular and cortical microarchitecture in subjects with fractures [3,5,6,[12][13][14], and previous in vivo studies that reported that trabecular bone microarchitecture is significantly associated with nonvertebral [15,16] and vertebral fractures [17][18][19][20]. The slightly better resolution of the hr-pQCT compared to previous techniques allowed us to extend these prior observations with presumably more accurate assessment of cortical and trabecular microarchitecture.…”
Section: Discussionsupporting
confidence: 80%
“…Our results confirm and extend previous ex vivo studies on iliac crest bone biopsies that showed alterations of trabecular and cortical microarchitecture in subjects with fractures [3,5,6,[12][13][14], and previous in vivo studies that reported that trabecular bone microarchitecture is significantly associated with nonvertebral [15,16] and vertebral fractures [17][18][19][20]. The slightly better resolution of the hr-pQCT compared to previous techniques allowed us to extend these prior observations with presumably more accurate assessment of cortical and trabecular microarchitecture.…”
Section: Discussionsupporting
confidence: 80%
“…(13,14) In a study comparing 107 women with and 107 women without prevalent wrist fracture and using pQCT at the radius, the trabecular volumetric BMC and BMD data seemed to discriminate fractured and nonfractured cases better than cortical area and vBMC. (40) In another crosssectional study, 21 women with a recent wrist fracture were compared with a control group with no history of fracture and similar volumetric total BMD at the distal radius using pQCT. The average trabecular hole size was larger in women with fracture than in controls, but the connectivity index was not significantly different between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous reports of a stronger association of forearm fractures with BMD assessed at predominantly trabecular sites. (35)(36)(37)(38)(39) Although the latter observation has led to the notion that distal forearm fractures stem mostly from trabecular bone loss, cortical bone strength makes an important contribution to forearm fracture risk as indicated by ex vivo studies. (40) In this analysis, cortical bone carried >60% of the load on the radius, and cortical thickness and area were 33% less and 29% less, respectively, in fracture cases compared with controls.…”
Section: Discussionmentioning
confidence: 99%